Interventional factors influencing natural killer cell immunity in colorectal cancer: a systematic review - Wai Sinn Soh; Grace L. Burns; Tharindu Senanayake; Raquel Cameron; Kerith Duncanson; Guy D. Eslick; Sharmila S. Prasad; Stephen R. Smith; Simon Keely (Cancer Immunology, Immunotherapy)
Abstract Background and aim Colorectal cancer (CRC) is the third most common cancer globally. Despite advances in curative CRC surgery, metastatic disease remains a significant problem. Emerging evidence suggests that several commonly used perioperative interventions may influence cancer immunity through natural killer (NK) cell function or numbers. This systematic review aimed to identify the effects of standard perioperative interventions on NK cells in CRC patients. Methods A systematic search of four databases, MEDLINE, EMBASE, Cochrane Library and Scopus was performed up to 30th July 2024 using keywords associated with colorectal cancer, NK cells and perioperative medications. PRISMA guidelines were followed. Critical appraisal was undertaken using the Joanna Briggs Institute Critical Appraisal tools for quasi-experimental studies and randomised controlled trials. Results The literature search identified 10,404 titles and abstracts for screening. Of these, 226 full-text papers were reviewed, and 16 studies were included for data extraction. Results were presented in a narrative synthesis due to study heterogeneity. In vivo studies consistently demonstrated a post-operative decrease in overall cytotoxic capacity and number of NK cells compared to pre-operative levels. This effect was observed across all examined medications, including fentanyl, morphine, propofol and oxycodone. Additionally, blood transfusion also resulted in decreased NK cell cytotoxicity and activity in CRC patients. Conclusion While surgical stress is one of the significant factor influencing NK cell cytotoxicity, this review indicates that perioperative intervention also contributes to decreased NK cell cytotoxicity. Our findings demonstrate that certain perioperative interventions (such as ketamine and morphine) can negatively impact NK cell cytotoxicity.